Genetic and Phenotypic Parameters of Body Weight in Ettawa Grade Goats - F Hasan; . Jakaria; A Gunawan (Faculty of Animal Science, Bogor Agricultural University, 2014)
The aim of this study was to estimate genetic and phenotypic parameters of growth traits consisting of birth weight (BW), weaning weight (WW), 6 mo body weight (6WM), 12 mo body weight (12WM), and 18 mo body weight (18WM) of Ettawa Grade goats. The number of goat used to determine growth traits of BW, WW, 6WM, 12WM, and 18WM were 316; 316; 259; 259 and 165 heads, respectively. Data were analyzed using General Linear Model (GLM) to identify non-genetic effect. Estimation of genetic and phenotypic parameters including heritability, repeatability, genetic and phenotypic correlation were calculated using Restricted Maximum Likelihood and GLM. Genetic trends were calculated using the regression of mean breeding values on birth year. The results showed that parity and type of birth had significant (P<0.05) influence on all growth traits. Estimated heritability of birth, weaning, 6WM, 12WM, and 18WM were 0.54±0.12; 0.35±0.07; 0.37±0.09; 0.68±0.16 and 0.63±0.19, respectively. Estimated repeatability of WW, 6WM, 12WM and 18WM, WW, 6WM, 12WM and 18WM were 0.98±0.01; 0.97±0.01; 0.94±0.03; 0.71±0.12 and 0.91±0.04, respectively. The genetic trends for traits of BW and 18MW were decreased fluctuatively. However, the WW, 6MW, 12MW were increased fluctuatively. The high and positive genetic correlations between all growth traits and 12WM traits in this study indicated that selection for high 12WM will improve genetic merit in Ettawa Grade goats. Key words: body weight, EBV, Ettawa Grade goat, genetic and phenotypic parameters